2008
DOI: 10.1590/s0080-62342008000100007
|View full text |Cite
|
Sign up to set email alerts
|

Integralidade do cuidado na saúde: indicações a partir da formação do enfermeiro

Abstract: RESUMENEl estudio tiene como objetivo entender la formación de las enfermeras para el cuidado integral. Los datos fueron obtenidos de entrevistas con profesores, estudiantes y enfermeras del servicio sometidos a análisis de discurso. Fue reconocida la comprensión de la integralidad del cuidado en la perspectiva de un modelo de atención a la salud que tiene como orientación el cuidado centrado en el usuario. Suscitaron reflexiones sobre las tecnologías y la forma de organización del trabajo, expresadas por una … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
62

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(85 citation statements)
references
References 6 publications
0
23
0
62
Order By: Relevance
“…Para que o cuidado ao doente de TB seja feito em observância ao princípio da integralidade, é necessário que o sentido do trabalho em equipe seja construído no processo de formação do profissional de saúde e nele sejam estabelecidas estratégias de aprendizagem que favoreçam o diálogo, a troca, a transdisciplinaridade entre os distintos saberes (14) . Nesse sentido, embora se reconheça que a pluralidade do conhecimento favoreça ao controle da doença, depoimentos revelaram que a enfermeira centraliza as ações de cuidado ao doente de TB.…”
Section: Salientamos Que Em Ambas As Modalidades De Produzir O Cuidadunclassified
“…Para que o cuidado ao doente de TB seja feito em observância ao princípio da integralidade, é necessário que o sentido do trabalho em equipe seja construído no processo de formação do profissional de saúde e nele sejam estabelecidas estratégias de aprendizagem que favoreçam o diálogo, a troca, a transdisciplinaridade entre os distintos saberes (14) . Nesse sentido, embora se reconheça que a pluralidade do conhecimento favoreça ao controle da doença, depoimentos revelaram que a enfermeira centraliza as ações de cuidado ao doente de TB.…”
Section: Salientamos Que Em Ambas As Modalidades De Produzir O Cuidadunclassified
“…It should be stressed that the study subjects' understanding of comprehensiveness refers to the principle of assisting the demands and health needs of the population, which results in comprehensive care. A previous study (18) showed that the participants understand comprehensive care as a presupposition to meet the biopsychosocial, spiritual and emotional needs of the population, including their sufferings, fears, financial and family problems, justifying that the characteristic of comprehensiveness in terms of health care, is made effective when users, with all their needs, meet a health professional with the required knowledge or resources to help solve their problems. The statements showed that when the interviewees met with users, they were taken by feelings and emotions, which sometimes hindered and sometimes facilitated their application of their professional knowledge with a view to interpreting the demands presented by the used.…”
Section: Resultsmentioning
confidence: 99%
“…The study subjects raise the issue of addressing health care practices that value the subjective dimension, which implies to develop a model for health care and education that recognizes individual aspects without disregarding the collective aspects, which should also be centered on the person who is receiving that care (18) . To do this, health education should aim at changing professional practices as well as the organization of health work (22) .…”
Section: (E30)mentioning
confidence: 99%
“…Também no modelo de formação dos profissionais de saúde houve repercussões. 9 Atendendo a esse movimento, as Diretrizes Curriculares Nacionais (DCN) para os cursos de graduação na área de saúde, publicadas em 2001, passam a servir como referência para a construção dos Projetos Políticos-pedagógicos pelas escolas. A promulgação das DCN representou um marco legal, ético e político no direcionamento da formação dos profissionais enfermeiros expressando expectativas de mudanças no processo de formação em consonância com o Movimento da Reforma Sanitária brasileira e o SUS.…”
Section: Introductionunclassified